Metastasis of clear cell renal cell carcinoma to the larynx a short literature review and presentation of a rare case of prolonged survival = Metastaza svjetlostaničnog karcinoma bubrežnih stanica u grkljan : kratki literaturni pregled i prezentacija rijetkog slučaja produljenog preživljavanja - Vrebac, Ilinko; Braut, Tamara; Marijić, Blažen; Zahirović, Dag; Dekanić, Andrea; Vukelić, Jelena; Maršić, Matej; Velepič, Marko M. (2021)
Renal clear cell metastatic carcinoma of the larynx is an extremely rare diagnosis with poor survival. The objective of this short review is to provide insight into current state of literature on this rare neoplasm. Additionally we include the case of a patient with metastatic process of the thyroid cartilage that was treated with novel targeted therapies which enabled prolonged survival and good quality of life. These findings support their inclusion in treatment protocols of patients with metastatic renal clear cell carcinoma of the larynx, especially in those refusing surgery which is the main treatment option in literature so far.
Metastaza svjetlostaničnog karcinoma bubrežnih stanica u grkljan izuzetno je rijetka dijagnoza s lošim preživljavanjem. Cilj je ovog kratkog preglednog članka pružiti uvid u trenutno stanje literature o ovoj rijetkoj novotvorini. Uz to uključujemo i slučaj pacijenta s metastatskim procesom tiroidne hrskavice koji je liječen novim ciljanim terapijama koje su omogućile produljeno preživljavanje i dobru kvalitetu života. Ova otkrića potkrepljuju njihovo uključivanje u protokole liječenja pacijenata sa svjetlostaničnim metastatskim karcinomom grkljana, posebno kod pacijenata koji odbijaju kirurško liječenje, što je dosad glavni modalitet liječenja prema dostupnoj literaturi.
Bibliografija: 19 jed.
Abstract ; Sažetak.
Keywords: Karcinom bubrežnih stanica -- Svjetlostanični karcinom -- Grkljan -- Ciljana terapija -- Metastaze -- Kvaliteta života